What works in schools : translating research into action - Marzano, Robert J. (Alexandria, VA : Association for Supervision and Curriculum Development, 2003)
Discusses the lessons education research has taught about what practices and factors make a difference in student achievement, covering school goals, curricula, student-teacher relationships, home environment, community involvement, instructional strategies, motivation theories, and other related topics.
"ASCD product no.: 102271"--T.p. verso.
Includes bibliographical references (p. 193-207) and index.
Bulletin (Center for Children's books).
The Science Teacher (N.S.T.A.).
Professional
Keywords: Academic achievement; School improvement programs; Teaching; Academic achievement; Schools -- Administration; Teaching